Investigation consumers behavior toward mobile payment intention among universities’ students in Klang valley - Khew, Yi Fei; Wong, Choon Fai (2019)
This study was aimed to investigate the consumers behavior toward mobile payment intention among universities’ students in Klang Valley. To specifically examine the in-depth of the mobile payment adoption intention, background and issues related to the research topic had been discussed. This study is designed to achieve the following objective: (1) To test out the relationships between the trust and the universities’ students adoption for the mobile payments intention; (2) To find out the significant relationships between the perceived usefulness and the mobile payment intention among the universities’ students; (3) To study of the relationships between the perceived ease of use and the universities’ students adoption to mobile payments intention; (4) To test the relationships between the social influence and mobile payment among the universities’ students. This research might also be beneficial to certain parties’ mobile payment service providers, shops that adopted mobile payment service, government, futur e researchers and consumers. Furthermore, reviews of literature by previous author and researcher are provided in order to further explain the association between the variables and the explanation of intention to adapt mobile payment technology. In this research, data were collected from primary sources where questionnaires are distributed to 200 respondents in 5 selected universities in Klang Valley area using Snowball sampling technique. Statistical Package for the Social Science (SPSS) software version 21.0 is used to carry out the research to construct new findings in the association between the independent variables and mobile payment adoption intention. The results and findings are then demonstrated in few different parts which included descriptive analysis for demographic profile, measurement of scale and the inferential analysis. Last but not least, all the findings in the research are concluded in the last chapter. Implication of the study are also further described, as well as the limitations. xvi Not to mention, several recommendations for future research are provided in order to sums up the entire completed research.